2020
DOI: 10.2319/013120-70.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the transfer accuracy of two digital indirect bonding trays for labial bracket bonding

Abstract: Objectives To compare the transfer accuracy of two digital transfer trays, the three-dimensional printed (3D printed) tray and the vacuum-formed tray, in the indirect bonding of labial brackets. Materials and Methods Ten digital dental models were constructed by oral scans using an optical scanning system. 3D printed trays and vacuum-formed trays were obtained through the 3Shape indirect bonding system and rapid prototyping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
77
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(90 citation statements)
references
References 15 publications
11
77
1
1
Order By: Relevance
“…Torque showed the worst transfer accuracies of all angular dimensions, and the same result was found in previous studies [ 5 , 7 , 14 , 16 ]. Nui et al refer to an excess of bonding material or the transfer tray design to explain the outcome for torque [ 16 ]. Most investigations though, lack an explanation for these results.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Torque showed the worst transfer accuracies of all angular dimensions, and the same result was found in previous studies [ 5 , 7 , 14 , 16 ]. Nui et al refer to an excess of bonding material or the transfer tray design to explain the outcome for torque [ 16 ]. Most investigations though, lack an explanation for these results.…”
Section: Discussionsupporting
confidence: 90%
“…In our, and in previous studies, the greatest transfer inaccuracies in the linear dimension were found in the vertical direction [ 5 , 6 , 7 , 8 , 16 ]. Inconsistent pressure on the tray during the bonding process is often mentioned as an explanation for this [ 5 , 6 , 7 , 16 ]. Most authors found that the deviation was towards the occlusal direction.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations